2014
DOI: 10.1038/jhh.2014.34
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a DASH-like diet containing lean beef on vascular health

Abstract: A DASH (dietary approaches to stop hypertension) dietary pattern rich in fruits and vegetables and low-fat dairy products with increased dietary protein provided primarily from plant protein sources decreases blood pressure. No studies, however, have evaluated the effects of a DASH-like diet with increased dietary protein from lean beef on blood pressure and vascular health. The aim of this study was to study the effect of DASH-like diets that provided different amounts of protein from lean beef (DASH 28 g bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 33 publications
5
33
1
1
Order By: Relevance
“…A DASH-style diet with six 100-g servings of lean beef/ wk reduced SBP/DBP by 6/4 mm Hg compared with consumption of a low-fat diet with #2 servings red meat/wk, which lowered SPB/DBP by 3/3 mm Hg (13). Collectively, results from the current, BOLD (12), and Nowson et al (13) studies showed that the inclusion of lean red meat in DASHstyle diets does not influence their effectiveness to reduce BP. In addition, results of the current study further support previous research that showed that diets rich in lean pork do not adversely affect cardiometabolic health compared with other animal sources of protein (21)(22)(23).…”
Section: Bpmentioning
confidence: 62%
See 2 more Smart Citations
“…A DASH-style diet with six 100-g servings of lean beef/ wk reduced SBP/DBP by 6/4 mm Hg compared with consumption of a low-fat diet with #2 servings red meat/wk, which lowered SPB/DBP by 3/3 mm Hg (13). Collectively, results from the current, BOLD (12), and Nowson et al (13) studies showed that the inclusion of lean red meat in DASHstyle diets does not influence their effectiveness to reduce BP. In addition, results of the current study further support previous research that showed that diets rich in lean pork do not adversely affect cardiometabolic health compared with other animal sources of protein (21)(22)(23).…”
Section: Bpmentioning
confidence: 62%
“…However, at least 2 studies assessed the effects of including lean beef in a DASHstyle diet on BP responses (12,13). In the BOLD (Beef in an Optimal Lean Diet) study, SBP was decreased by 4 mm Hg after the consumption of a DASH-style diet with 153 g lean beef/d but was not decreased after DASH-style diets with 113 or 28 g lean beef/d, and DBP was not influenced by any of the 3 DASH-style diets (12). The BOLD study was conducted in normotensive subjects, whereas the majority of DASH-style diet interventions have studied individuals with elevated BP (6).…”
Section: Bpmentioning
confidence: 99%
See 1 more Smart Citation
“…The American beef industry has produced many products that meet the USDA definition of "lean" which is defined as containing no more than 10 g total fat and 4.5 g of saturated fat in a serving of approximately 100 g. In fact, controlled feeding intervention studies have clearly shown reductions in risk factors for heart disease, such as total cholesterol, LDL-cholesterol, apolipoproteins A-I and C-III, and systolic blood pressure, as well as the augmentation index -a measure of vascular reactivity (Roussell et al, 2012(Roussell et al, , 2014. A meta-analysis of 124 RCTs on lipid and lipoprotein changes comparing beef against poultry or fish consumption found no significant differences (Maki et al, 2012).…”
Section: Epidemiology Of Meat and Healthmentioning
confidence: 99%
“…Дієта має бути збагаченою вітамінами групи В, С, хромом, карнітином, таурином, ліпоєвою кисло-тою. У цих хворих також використовуються адапто-вані Mediterranean та DASH-дієти, дієти Polymeal, Omni Heart, клініки Майо, Weight Watchers, що, крім вагокорегуючих ефектів, мають протизапальну активність, знижуючи рівні С-реактивного протеїну та цитокінів [35,37,40].…”
Section: огляд / Reviewunclassified